2021
DOI: 10.1016/j.tranon.2021.101084
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and molecular portrait of non-metastatic anal squamous cell carcinoma

Abstract: Highlights High-risk HPV infection is less frequently detected in HIV-positive non-metastatic ASCC compared with HIV-negative cases. Mutational profile identified in the non-metastatic ASCC cohort revealed expected similarities with metastatic ASCC. High PD-L1 expression levels are associated with high CD3 and CD8 TIL density, complete response to treatment, and good survival outcome of ASCC patients. PD-L1 is a reliable predictive and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Tumor infiltrating lymphocytes may be of superior prognostic value for anal cancer (30) and will be prospectively evaluated in the PLATO study (ISRCTN88455282). Additional biomarkers under investigation include circulating tumor HPV DNA (31,32) and PD-L1 (33). Only a minority of patients in this study were treated with MMC, potentially limiting the generalizability of our results.…”
Section: Parametersmentioning
confidence: 96%
“…Tumor infiltrating lymphocytes may be of superior prognostic value for anal cancer (30) and will be prospectively evaluated in the PLATO study (ISRCTN88455282). Additional biomarkers under investigation include circulating tumor HPV DNA (31,32) and PD-L1 (33). Only a minority of patients in this study were treated with MMC, potentially limiting the generalizability of our results.…”
Section: Parametersmentioning
confidence: 96%
“…Racial disparity in stage distribution and survival is multifactorial and is reported to be due to socioeconomic factors, insurance status, comorbidities, and tumor characteristics. 31 Studies by Iseas et al, 19 Wessely et al, 22 Balermpas et al, 32 and Chamseddin et al 33 showed better survival rates from ASCC in PD-L1 þ patients. Mitra et al 24 did not find PD-L1 to be prognostic but found a different biomarker, indoleamine 2,3 dioxygenase 1 (IDO1), to be associated with poor outcome.…”
Section: Pd-l1 Expression and Outcomesmentioning
confidence: 97%
“…of viable tumor cells] 3 100) of 1% or higher was defined as PD-L1 positive (PD-L1 þ ) in the Keynote-028 clinical trial 16 and has also been used in a few other studies. 16,[18][19][20] Because other studies evaluating PD-L1 in anal cancer have used TPS, we also evaluated TPS. [21][22][23][24][25] Tumor proportion score is the percentage of viable tumor cells showing partial or complete membrane staining and of any intensity…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations